Pemanfaatan Minyak Jelantah Dalam Pembuatan Lilin Aromaterapi di Desa Bandar Baru Kecamatan Sibolangit - Utami, Tri Niswati; Kudadiri, Nazli Ba’iah; Komaruddin, Niswah Zhafira; Syafitri, Najla Rifda; Farahany, Suci; Amri, Nurul Fadia (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
Used cooking oil is a household waste that is often disposed of carelessly, causing negative impacts on health and the environment. The high volume of used cooking oil waste in Bandar Baru Village, Sibolangit District, and the lack of public awareness about the dangers of reusing oil and improper waste disposal, prompted the initiative to utilize this waste into a marketable product. This community service activity aims to increase public knowledge about the impact of used cooking oil, provide skills in making aromatherapy candles from used cooking oil, and encourage creative business potential. The method used is socialization and direct training for mothers in Bandar Baru Village. The results of the activity show an increase in public awareness and skills in processing used cooking oil into aromatherapy candles, as well as the potential of this product as an additional source of income and a solution to environmental pollution.